Poison to the Beasts: Changing Poisons and Poisoning Practices in Campaigns to Kill Norwegian Birds and Mammals, 1845-1967. (1st August 2019) - Ohman Nielsen, May-Brith; Seines, Anne Mette
Between 1845 and 1967 deadly poison was often used to kill and eradicate unwanted wild animals in the Norwegian fauna. The major targets of these poison practices were rats, predators and crows. This article presents the main types of poisons used, the main methods of poison administration and the legislation covering the poisoning-practices in regards to the various species, as well as negotiations over the killing methods and wildlife eradication programmes. Examining the changing social and political organisation of these eradication campaigns brings new insights into the cultural history of poison, into the cultural relations between man and nature and into changing human ideas of safety and danger. We suggest that practices of intentional killing by poisoning of larger animals impinged upon attitudes towards direct or indirect poisoning of insects and concern over toxic risks.